A new approach to control elastic joint robots with application to adaptive control - Nicosia, S.; Tomei, P. (IEEE Decision and Control, 1991, 1991)
A new approach to control robots having elastic joints is presented. The control law guarantees global asymptotic stability of the closed loop system either for regulation about a reference point or for tracking of a desired bounded reference trajectory. It is shown that this approach may be applied to derive globally convergent adaptive control algorithms. This is illustrated by an application of the proposed approach to a simple robot consisting of a single-link revolute jointed manipulator with flexibility in the joint.< >